Solusi Ketahanan Pangan dan Peningkatan Ekonomi Rumah Tangga Melalui Inovasi Budikdamlon (Budidaya Ikan Lele dan Kangkung dalam Galon) - Zulfa Intania; Ayu Fadhillah; Fahmi, M. Alfin; Dian Rif'iyati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The increasing need for food, especially vegetables and meat, is a major societal challenge. One promising solution is to utilize backyard land through an aquaponics system. This study was carried out in Sumurjomblangbogo Village, Bojong District, Pekalongan Regency, to empower PKK women in cultivating catfish and water spinach using Le Minerale gallons. The aquaponics system that was implemented combines fish cultivation with hydroponic plants in a recirculation system, utilizing fish waste as plant fertilizer. Implementation methods include outreach, training, and assistance to the community. The results show that this cultivation system effectively increases family food security and community economic welfare. The Le Minerale gallon allows optimal use of narrow land with a monthly harvest of kale and catfish in 2-3 months. This system is efficient in land and water use and can be implemented at low cost. This activity succeeded in increasing community knowledge and skills in managing natural resources in a productive and environmentally friendly manner, which can reduce household expenses and increase income by selling cultivated products. These findings provide a strong basis for developing aquaponic systems in other areas with similar conditions.